(NnA RAZNYH [IROTAHs - (NdROZDOW(B,(Nn(B. (Nn(B.s (NnIKOLAJ nIKOLAEWI^s; (NmAKEEW(B,(Na(B. (Nk(B.s (NaLEKSEJ kUZXMI^s ((Nm(B.s (NwE^Es, 2008)
(NkAM^ATKA $1 (S0(NSTRANA LXDA I OGNQ(S1(B, (NbADHYZ $1 (S0(NVEM^UVINA(S1 (NPRIRODY sREDNEJ aZII(B, (NBLAGOSLOWENNYJ kRYM(B, (N\KZOTI^ESKIE OSTROWA tIHOGO OKEANA(B, (NTROPI^ESKIE LESA aMAZONKI(B... (Nw KAVDOM IZ \TIH UGOLKOW NA[EJ PLANETY SWOJ NEPOWTORIMYJ MIR VIWYH SU]ESTW $1 (NPERNATYH I ^ETWERONOGIH(B, (NPOKRYTYH [ERSTX@ ILI ^E[UEJ(B, (NPRYGA@]IH(B, (NBEGA@]IH(B, (NPLAWA@]IH ILI LETA@]IH(B. (N~ITAQ \TU KNIGU(B, (NWY SMOVETE VIWO PREDSTAWITX SEBE \TOT UDIWITELXNYJ I PREKRASNYJ MIR(B, (NA TAKVE WSPOMNITX NEKOTORYE FRAGMENTY POPULQRNOJ TELEPEREDA^I (S0(Nw MIRE VIWOTNYH(S1(B.s